Governance through Translation: Policies and Practices in Brunei Darussalam - Yusof, Badriyah; Azalie, Izni Azrein (Bina Nusantara University, 2024)
The research investigated how translation functions as an object of governance in Brunei Darussalam, guided by the polysystem theory. Translation served as a critical component within the communication framework, affecting domains like education, economy, and information technology. Applying qualitative-descriptive methods, including experiential insights and observational data, the research explored how translation activities were regulated and integrated across government institutions to promote social cohesion, accessibility, and national development. In Brunei, translation was essential for ensuring effective communication in legal, health, and religious contexts. Key government entities, such as the Language and Literature Bureau and the Ministry of Religious Affairs, managed translation units to support these functions. The analysis underscored how translation aligned with the national objectives of Brunei Vision 2035, aiming at a high-quality education, improved quality of life, and a sustainable economy. Results reveal that effective translation practices foster social cohesion, equitable access to public services, and national development. Continuous assessment, technological advancements, and human resource development are crucial for maintaining and enhancing the effectiveness of translation as an object of governance. Brunei’s case sheds light on the transformative potential of translation as a powerful tool for governance and holistic development, fostering cultural preservation and inclusivity. The research significantly contributes to the broader discourse on how effective translation governance can facilitate sustainable national progress and cross-cultural understanding.